Consumer perceptions of environmentally and climatically significant food consumption : A focus group study in the Finnish context - Roininen, Taneli (Aalto University, 2012)
Food consumption is one of the areas which have the biggest impact on the environment; a little less than 30 percent of greenhouse gas emissions and around 50 percent of eutrophication of all household consumption accounts for food in Finland. The importance of the sustainable decision-making of the consumers is especially highlighted in the food sector, where in contrast to other sectors, significant greenhouse gas emission reductions cannot be achieved just by applying low-carbon-technology; significant reductions can be achieved only by changing the dominant consumptions patterns and the food-related behaviour of the consumers.Previous studies show that the consumers communicate positive attitudes toward sustainable decision making and they seem to have a true concern about the global sustainability issues. Still, they are struggling to translate the attitudes into consumption behaviour. Thus, there seem to be a clear and widely acknowledged attitude-behaviour gap. This study aims to explain the barriers to environmentally significant behaviour by building understanding on consumer perceptions of environmentally and climatically significant food consumption by studying consumer perceptions of five focus groups. A theoretical framework of the pro-environmental consumer behaviours and the environmentally significant food consumption was created, which was later on reflected to the findings of the focus groups. Additionally, the future direction for climate communication of food was identified. Based on the empirical results, it can be concluded that the current level of knowledge of the consumers related to environmental and climatic considerations of food is very poor. The consumers seem to have both false assumptions and knowledge of the environmental impacts and the sources of food. Furthermore, the consumers seem not to consider climate change as one of the most important environmental issues and the concept is carbon footprint was very poorly known. The information asymmetry was recognized to be the most significant single barrier to closing the attitude-behaviour gap. It seems that there is an urgent need for a wide education scheme to correct the great information asymmetry.
Diplomityö: Aalto yliopisto, 2012
Keywords: Elintarvikkeet, ravitsemus; hiilimerkinnät; ilmastovastuulliset asenteet; ympäristövastuullinen ruuankulutus; kuluttajakäyttäytyminen; ympäristöarvot; consumer behaviour; sustainability